Pengaruh Kompensasi Terhadap Prestasi Kerja Karyawan Pada Hotel di Kota Ketapang (Kab. Ketapang Kalimantan Barat) - Fitria Elvi (Jurnal Ekonomi Integra, 2017)
Employee performance for the company as the last measure of the success of a personnel department dam has a strong relationship with the goals and success of a company. With the existence of compensation pemeberian then expected every employee feel satisfied with company kebiajakan and will impact to good work performance also.This study wanted to prove the influence of compensation on employee performance at hotel in ketapang city (Ketapang Kalimantan Barat). Based on previous research and related to the supporting theory put forward by experts by using SPSS 21 program, as a tool of statistical data processing.This type of research is Causal explanatory is a type of research that aims to determine the pattern of relationships between variables as a hypothesis testers. This research was conducted in the town of Ketapang Kalimantan Barat. With some population and 60 hotel employees as sempel in this research with data analysis using simple linear regression analysis technique.Based on the data processing using simple linear regression proved that the variable (X) compensation effect positively and significantly to the variable (Y) Employee performance at the hotel in ketapang city (Ketapang, Kalimantan Barat).